Micromechanical analysis of dentin/adhesive interface by the finite element method - Marangos, Orestes; Spencer, Paulette; Wang, Yong; Katz, J. Lawrence; Misra, Anil S. (My University, 2004)
The interfacial microstructure and spatial distribution of the modulus of elasticity have a profound effect on load transfer at the dentin/adhesive (d/a) interface. The microstructure is influenced by the varying degree of demineralization of intertubular and peritubular dentin during etching as well as the depth of adhesive penetration into the hybrid layer. These factors lead not only to a unique microstructure in the vicinity of the dentinal tubules, but also to a mechanically graded hybrid layer. This article investigates the micromechanical stress distribution at a d/a interface with the use of finite element analysis (FEA). Such analysis is now feasible given the newly measured moduli of elasticity at micro- and nanoscales. The results indicate that the morphological and micromechanical properties of the d/a interface affects the stress field such that the fracture/failure is likely to initiate in the stress-concentration zone of peritubular dentin next to the hybrid/exposed- collagen layer. The results suggest that devising a full-depth high modulus hybrid layer may considerably reduce the stress concentration zone and the magnitude of stress concentration in the peritubular dentin next to the hybrid/exposed-collagen layer. © 2004 Wiley Periodicals, Inc.
Keywords: Collagen; Dentin/adhesive; Finite element; Interface; Micromechanics